An investigation of Wikipedia translation as an additive pedagogy for Oshikwanyama first language learning - Hautemo, Aletta Mweneni (Rhodes University, Faculty of Education, Department of Education, 2014)
The integration of Information and Communication Technology in the indigenous language classroom lags behind compared to other subjects. In many ways, indigenous language teachers find it difficult and to some extent, impossible to integrate ICT into their classroom activities. The focus of this study is to explore the ways in which ICT could be used as a learning tool in an Oshikwanyama First Language classroom. I investigated the use of Wikipedia translation as an additional teaching and learning tool. I concentrated on the impact that ICT tools have on learning, and the motivation it has on learners to learn Oshikwanyama. This qualitative case study was conducted in an urban school in northern Namibia. The adoption of ICT at the school is good as there is a full-fledged computer lab with unlimited wireless internet access. This was a requirement for the project to enable the participants to work online. I purposefully chose higher-level learners (Secondary phase) for this study. I conducted a survey with them on their access to and use of ICT devices in their daily lives, and thereafter conducted a basic computer workshop and a Wikipedia translation project with them. My research findings show that although the use of ICT is part of the learners' lives, most of the communication through ICT devices is done in English not Oshikwanyama. Wikipedia translation offers a stimulating learning platform for learners to learn Oshikwanyama and English at the same time and this improved their performance in both languages. Furthermore, the Wikipedia translation, which was done collaboratively, gave learners the confidence to work with other learners to create knowledge. Lastly, Wikipedia translation motivates learners to learn Oshikwanyama and use it in their daily ICT interaction.
Keywords: Kuanyama language -- Study and teaching (Secondary) -- Computer-assisted instruction; Kuanyama language -- Machine translating -- Namibia; Language and languages -- Study and teaching (Secondary) -- Computer-assisted instruction; Computer-assisted instruction -- Study and teaching (Secondary) -- Namibia; Information technology -- Study and teaching (Secondary) -- Namibia; Educational technology -- Namibia; Wikipedia